2017
DOI: 10.1016/j.stemcr.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Human Fibroblasts into Neural Progenitors Using Transcription Factors Enriched in Human ESC-Derived Neural Progenitors

Abstract: SummaryEarly human embryonic stem cell (hESC)-derived neural populations consist of various embryonic neural progenitors (ENPs) with broad neural developmental propensity. Here, we sought to directly convert human somatic cells into ENP-like phenotypes using hESC-ENP-enriched neural transcription factors (TFs). We demonstrated that induced ENP could be efficiently converted from human fibroblasts using two TF combinations. The iENPs exhibit cellular and molecular characteristics resembling hESC-ENPs and can gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…iNSCs are particularly suited for characterizing neural cells in health and disease, as well as during neural development. Moreover, treatment of patient-derived neuronal cultures with GSK3b inhibitors resulted in a significant reduction of pTAU aggregates [37]. Importantly, the iNSC-derived neuronal cell cultures recapitulated cellular hallmarks of the disease, including increased levels of amyloid ß and phosphorylated TAU (pTAU) in neuronal cell bodies and processes [37].…”
Section: Functional Characterization Of Insc-derived Neuronsmentioning
confidence: 99%
See 4 more Smart Citations
“…iNSCs are particularly suited for characterizing neural cells in health and disease, as well as during neural development. Moreover, treatment of patient-derived neuronal cultures with GSK3b inhibitors resulted in a significant reduction of pTAU aggregates [37]. Importantly, the iNSC-derived neuronal cell cultures recapitulated cellular hallmarks of the disease, including increased levels of amyloid ß and phosphorylated TAU (pTAU) in neuronal cell bodies and processes [37].…”
Section: Functional Characterization Of Insc-derived Neuronsmentioning
confidence: 99%
“…The unexpected reprogramming activity of this non-neurogenic TF critically depends on its interaction with RBPJ to activate downstream TFs involved in NSC specification. In 2017, Hou et al [37] reported two reprogramming protocols exploiting either six or seven TFs for direct OSKM-and BSKM-independent conversion of human fibroblasts into iNSCs. In 2017, Hou et al [37] reported two reprogramming protocols exploiting either six or seven TFs for direct OSKM-and BSKM-independent conversion of human fibroblasts into iNSCs.…”
Section: Transcription Factors Employed In Insc Generationmentioning
confidence: 99%
See 3 more Smart Citations